Eumelanin pigment precursor 2-carboxy-5, 6-dihydroxyindole and 2-amino-6-methylbenzothiazole chromophore integration towards melanin inspired chemoresponsive materials: the case of the Zn2+ ion. Issue 33 (21st July 2022) - Mocerino, Fabio; Pezzella, Alessandro; Caruso, Ugo
Abstract : The 2-amino-6-methylbenzothiazole chromophore is introduced at the carboxyl group of the melanin precursor 2-carboxy-5, 6-dihydroxyindole achieving a novel dihydroxyindole derivative with metal chelation properties not involving the catechol moiety. Abstract : The 2-amino-6-methylbenzothiazole chromophore is introduced at the carboxyl group of the melanin precursor 2-carboxy-5, 6-dihydroxyindole achieving a novel dihydroxyindole derivative with metal chelation properties not depending on the catechol moiety. In view of potential exploitation in charge storage systems, systematic investigation of the interaction of the new amide derivative with metal ions is carried out, in comparison with that of the parent 2-carboxy-5, 6-dihydroxyindole, and the stoichiometry of the zinc-amide complex is determined.